Edukasi Terkait Foto Produk Untuk Pengembangan Usaha Mikro Desa Amansari - Candra Hidayat; Kusnadi (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
In this day and age, many things are changing rapidly, such as the way in which product promotions are presented. In Indonesia, micro (small) business products tend to have started following the development of creative and innovative product promotions, especially on social media. In addition to promotion, micro-enterprises also use social media as a medium for transactions. However, the ability to manage promotions is still very rarely owned by micro business actors, especially micro business owners in Amansari Village, Rengasdengklok District, Karawang Regency. This is the reference for the team to carry out community activities in terms of "Photography and Design" using tools that are always available in every home, affordable and easy to find and produce photos and competitive product designs in a promotion. Education and training will begin with material or theory and then continue to practice directly with existing equipment so that the community is able to directly implement the new knowledge that has been obtained.